Unveiling the role of lncRNA ERDR1 in immune cell regulation - Aihua Shu; Xu Tian; Jie Yue; Yuxia Jiang; Yifei Liu (Heliyon)
Long non-coding RNAs (lncRNAs) are a class of RNA molecules that exceed 200 nucleotides in length and lack the capacity to encode proteins. In recent years, there has been a surge of interest in lncRNA research, leading to the discovery of their diverse structures and functions. This review focused on elucidating the regulatory roles of lncRNA erythroid differentiation regulatory 1 (Erdr1) within immune cells and its involvement in related disorders. By synthesizing findings from recent studies sourced from PubMed, this paper examined the biological functions and underlying mechanisms by which lncRNA Erdr1 influences immune cells and contributes to various diseases. Emerging research highlights that lncRNA Erdr1 exerts significant effects on the functionality of immune cells, particularly T lymphocytes (T cells), natural killer (NK) cells, and macrophages. Furthermore, Erdr1 has been implicated in the mitigation of several diseases, including acne, wound healing, osteoarthritis, melanoma, gastric cancer, obesity, and autism. Given its complex biological functions and mechanisms, Erdr1 presents itself as a promising biomarker and a potential therapeutic target for a range of immune cell-related disorders.